PHC-003 Assessment of the Impact of Pharmacokinetics Monitoring Recommendations. (12th March 2013) - Moreno, M; Casado, C; Rodriguez, P; Vázquez, R; Molina, T
Abstract : Background: In our general hospital, with 450 beds, the Pharmacy department (PD) has a pharmacokinetics area in which vancomycin and aminoglycosides are monitored in non-critical adult patients. The monitoring starts when: There is a medical request (MR). Or a pharmaceutical proposal (PP) is made followed by medical acceptance (MA) Purpose: To determine and quantify the acceptance of monitoring recommendations made by the PD, to assess the recommendations and describe PP monitoring. Materials and Methods: Prospective and descriptive study. We collected patients treated with vancomycin or aminoglycosides over a 3-month period (March-June/2012), excluding those for whom there was an MR. Patients included in our study were divided into two categories: monitoring was recommended and not recommended. Criteria for recommended monitoring: GFR < 60 ml/min, >5 days' treatment, geriatric, obese or concomitant nephrotoxic drugs. Recommendation was made through the electronic prescription programme with the appropriate justification. If a positive answer was not obtained in two days, it was considered as 'not accepted'. Patients requiring dose adjustments and the mean number of dose adjustments necessary to achieve appropriate plasma concentrations were also recorded. Results: View table. Due to pharmaceutical intervention, 19.6% patients were monitored, the majority of them with vancomycin (13.3%). Conclusions: Pharmacy recommendation is an instrument to strengthen monitoring of certain drugs in some situations. Because gentamicin is used mainly in surgical prophylaxis, the number of patients who might need monitoring was low. Out of range initial concentrations with vancomycin and amikacin, might indicate an inappropriate dosage. The low number of adjustments per patient showed that the correct pharmacokinetic calculations had been made by the PD. No conflict of interest.